Pengaruh Kondisi Keuangan, Ukuran Perusahaan dan Perencanaan Pajak terhadap Manajemen Laba pada Perusahaan yang Terdaftar di Bursa Efek Indonesia - Anandita Zulia Putri; Rahandhika Ivan Adyaksana; Vidya Vitta Adhivinna; Monika Aprilia Suriyanti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The study aimed to examine how earnings management, particularly in transportation, utilities, and infrastructure companies listed on the Indonesia Stock Exchange (IDX), is influenced by tax planning, company size, and financial condition. The research method employed quantitative secondary data analysis using inner model analysis and processed with SmartPLS 4.0. The study population comprised transportation, utilities, and infrastructure companies listed on the IDX between 2017 and 2021, with a total of 52 companies as samples, resulting in 243 data points collected for this study. The results showed that financial condition had a positive impact on earnings management, while company size had a negative impact. Tax planning had no effect on earnings management. The study population comprised transportation, utilities, and infrastructure companies listed on the IDX between 2017 and 2021, with a total of 52 companies as samples, resulting in 243 data points collected for this study. This broad sample size enhances the reliability of the findings, ensuring that they are representative of the sector as a whole. The data was gathered from publicly available financial statements, offering an accurate reflection of the companies' financial performance over the period in question. The results showed that financial condition had a positive impact on earnings management, suggesting that companies in better financial health are more likely to engage in earnings management practices. On the other hand, company size had a negative impact, indicating that larger companies may be subject to stricter regulatory scrutiny, thus limiting their ability to manipulate earnings. Interestingly, tax planning had no effect on earnings management, possibly indicating that companies may not view tax strategies as a significant driver of earnings management practices.